Slovenski jezik od Slomška do Grmiča - Jesenšek, Marko (Časopis za zgodovino in narodopisje, 2023)
In this discussion, the author presents Grmič’s attitude towards the Slovenian language, upbringing, and education, as he came to know it during his “encounters” with Slomšek, and then mapped it onto “his” 20th century, so that he experienced it inwardly and perceived its lasting spiritual significance for the Slovenes’ self-determination, and attributed timeless values to it.
Keywords: Grmič, Vekoslav; izobraževanje; jezik; razumevanje jezika; Slomšek, Anton Martin; slovenščina; sporazumevanje; vzgoja; zgodovina jezika